Designing Interdisciplinary, Early Intervention Dispute Resolution Tools to Decrease Evictions and Increase Housing Stability - Christine N. Cimini (Washington University Journal of Law and Policy, 2023)
This Article provides a unique glimpse into the development of an early- intervention, pre-court, interdisciplinary dispute resolution project intended to decrease evictions and increase housing stability for recipients of subsidized housing in Seattle. With a grant from the Seattle Housing Authority (SHA), a coalition of non-profit organizations had the rare opportunity to design a dispute resolution system into existence. A dispute system design team was formed and began by examining the interconnected problems of housing instability, eviction, and houselessness. Despite thorough research on dispute system design and extensive meetings with stakeholders, the deign team encountered numerous challenges. This Article identifies the design challenges specific to this project, as well as the larger systemic issue of actual fairness underlying all dispute resolution tools. Mindful of these issues, the design team created a program titled Conflict Resolution Services (CRS). CRS is rooted in six key components: consistent outreach and ongoing education; rapid response de-escalation; integration of social services support; proximity to the conflict; development of an interdisciplinary, multicultural team; and research and assessment to create an iterative process of continuous re-design. After providing a brief overview of the preliminary qualitative and quantitative research design component of CRS, the essay concludes by explicating and contextualizing three key insights derived from the dispute system design process. First, take the time needed to engage in a thoughtful and holistic design process. Second, despite inherent challenges, engage, collaborate and rely on the expertise of other organizations. Finally, recognize and acknowledge systemic issues facing all dispute resolution systems such as power imbalance, inequality, racism, and implicit bias and seek creative solutions to overcome challenges.
Keywords: housing stability; homelessness; houselessness; early-intervention; interdisciplinary; dispute resolution; conflict resolution; intervention; public housing; systemic issues; power imbalance; inequality; racism; implicit bias